Phylogenetic and genetic diversity analysis in Leptospira species based on the sequence homology pattern of 16S rRNA gene - Rao, Pasupuleti Sreenivasa (International Journal of Research in Medical Sciences, 2017)
Leptospirosis is a bacterial zoonosis, caused by pathogenic spirochete which belongs to the genus Leptospira. It exists in diverse ecological habitats and affects almost all the mammals including humans. Several online databases like NCBI etc will provide the complete genomic sequence data of various Leptospira species. However, the Phylogenetic and genetic diversity Analysis in Leptospira species based on 16S rRNA gene has not studied in detail. Therefore the present study was conducted. Sequences of various species related to genus Leptospira obtained from the NCBI database etc and aligned (CLUSTAL_X). Two Phylogenetic trees were constructed (MEGA-5) in which the first one is related to various serovars of L. interrogans and the other is related to various species of Leptospira. The Phylogenetic trees revealed the relationship and genetic diversity of various serovars of L. interrogans and the other Leptospira species, with their nearest phylogenetic relatives. In the first tree, two major clades were observed which were named as A and B, whereas in the second tree, three major clades were observed and named as A, B and C respectively. Aquifex pyrophilus strain has been used for out grouping in both the trees. The genetic distance between the species in the phylogenetic tree is presented by a bar which represents 0.5 nucleotide substitutions per alignment position in the 16S rRNA gene sequence among the various serovars of L. interrogans while 0.05 nucleotide substitutions in case of various species related to the genus Leptospira. Thus, the findings from the above study confirm that the genus Leptospira exhibits genetic diversity in the 16S rRNA gene.